Crystallographic fusion behavior and interface evolution of mono-layer BaTiO3 nanocube arrangement. Issue 9 (5th February 2016) - Ma, Qiang; Kato, Kazumi
Abstract : An abnormal sintering behavior between BaTiO3 nanocubes with variable sintering temperature and geometry was investigated by high resolution transmission electron microscopy. Abstract : A crystallographic fusion behavior between BaTiO3 nanocubes with variable sintering temperature and geometry was investigated by precise analysis using high resolution transmission electron microscopy (HRTEM). The fine orderly microstructure of the nanocube arrangement was retained even after a high temperature sintering process (∼900 °C), where the face-to-face connection with a simple cubic symmetry was stable. By using FFT filtered HRTEM images, we revealed the atom-scale crystalline coherence of neighboring BaTiO3 nanocubes in the connection. In the case of the small angle relation of nanocubes, the initial ambient interface changed into a robust structure at one critical sintering temperature, and the final lattice defects evolved in the interface region. The lattice fringes in different nanocubes grew and connected via an atom-by-atom epitaxial attachment mechanism, and a semi-coherent fusion region was formed around 850 °C. The amount of defects has a close relationship with the sintering temperature. Combined with the results of our previous research, the evolved nano-architecture consisting of the ordered nanocubes and interfaces plays a key role in the enhancement of dielectric properties.